(3SLY GdbeQjI aj QHY eOQSI GdbeQjIs - (3GdMSjfj GdBdhSj, CHh GdKfGA, TgGH GdOjf, eMehO Hf YHO Gddg Hf eMehO Hf OQhjT, J (B1270 (3g`s
(3ChdgG (B:s
(3HSe Gddg Ndjdj Ef GdMH eG JYQaGfg adG JfcQG Cf GdMfjf ef GdhLO (B, (3GYde CjgG GdNdjd GdNdj P GdaVd GdLdjd GdLdj Cfg bO GJab dj aj GeQ GdYTb CZQH bUI hdYeQj dbO MdJ hEf eQJ s
(3BNQgG (B:s
(3hbO GSJXd ajg HXdGd GdfUM hbGd jG Hfj Ydi GSJjaGA GdhUGjG dG Cbhi hLeGY Pdc ajeG CQi GdJbhi aGdJbhi GdJbhi hdjCJ CMOce efgG HeG jbhi Jes
(3ebGHdI HCUdg Ydi jO eDdags
(3JHUQI GdYfhGf (B:s
(3dYdgG ef GdebGeGJ GdePchQI aj JQLeJg aj GdCYdGe hgOjI GdYGQajfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\176s
(3gOjI GdYQajf (B2\419s
Keywords: (3GdCOHs